TRANSFORMASI EKS BADAN KREDIT DESA MENJADI UNIT USAHA BUMDESA BERSAMA KABUPATEN BANYUWANGI - Emi Hidayati (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2018)
This community service is backed by the dynamics of the implementation of POJK No. 10/2016 on the transformational former BKD, while given the status as a BPR, in which the institutional ownership process has been denied opposition between Old managers who feel that they have been running a unit of borrowing with capital from the BRI and not from the village government with the villagers who feel they have the opportunity to manage the government's own inherited financial institutions. Although many of the village governments do not understand its regulation. This community service aims to get a picture of the transformation model of BKD into a business unit of BUMDesa Bersama. After obtaining supporting data through the examination of documents, participatory observation and indept interview, get the result that from 86 BKD in Banyuwangi district, 63 villages have implemented management cooperation in the container of BUMDesa Bersama, 2 The village chooses to manage in the form of BUMDesa, and 1 village has not determined the choice, while the 20 BKD in the village has not been able to determine transformation options because it has not obtained the legal certainty.